Immunoglobulin-mediated immune dysregulation in recurrent pregnancy loss: mechanisms, biomarkers, and therapeutic perspectives - Kamala C; Pallavi Shekar; Umme Kulsum; Ananya Hegde; Lakshitha V Jayakrishna; Deepa Bhat; Meghana Hangala Shivakumaraswamy; Akila Prashant; Praveen Kumar K S (Immunologic Research, 2026)
Recurrent pregnancy loss (RPL) is a multifactorial reproductive disease that is typified by repeated pregnancy loss with immune dysregulation emerging as a critical contributing factor. Immunoglobulins are among the immune components that are instrumental in preserving tolerance between the mother and the fetus, regulating inflammatory responses, and supporting placental development. This review provides a comprehensive overview of the role of immunoglobulins in recurrent pregnancy loss, with particular emphasis on immune dysregulation, emerging biomarkers, and therapeutic implications. The immunoglobulin profiles, such as the changes in IgG subclasses and the presence of pathogenic autoantibodies, e.g. antiphospholipid and antinuclear antibodies, are highly correlated with unfavourable pregnancy outcomes. These changes, in a mechanistic manner, lead to poor trophoblast invasion, endothelial dysfunction, thrombosis and cytokine imbalance. Emerging evidence also highlights the contribution of regulatory B cells and the antibody-mediated immune network in maintaining pregnancy homeostasis. Immunoglobulin profiling has clinical potential as a diagnostic and prognostic methodology that can be used to stratify patients and provide customised therapy. Immunomodulatory therapies, especially intravenous immunoglobulin (IVIG), are potentially effective in a limited range of patient populations, but clinical response is variable. On the whole, this review demonstrates the role of immunoglobulin-mediated mechanisms in RPL and their future potential in enhancing precision medicine approaches to better diagnosis and management.

Evaluation of Shatpada Fruit Fly Traps Versus Conventional Fruit Fly Traps in Citrus in India - Sandeep Singh; Srinivas Reddy; Ranjit Kadu; Y. V. Ingle; Sikha Deka; Raaj Kumar Kokoti; L. Ranjith Kumar; Aayush Kaushal; Deepa Bhagat; S. Priya Devi; Guranshpaul Singh; Ashok Kumar; et al. (Applied Fruit Science, 2026)

Sickle cell disease-related myths and misconceptions among tribal communities in India: a multi-state qualitative study - Yogita Sharma; Parikipandla Sridevi; Jatin Sarmah; Godi Sudhakar; Manoranjan Ranjit; Shaily B. Surti; Deepa Bhat; Madhusmita Bal; Rabindra K. Jena; Bontha V. Babu (Journal of Community Genetics, 2026)

Anti-osteoporotic potential of Lawsonia inermis leaf extract: integration of network pharmacology, molecular docking, and experimental validation in ovariectomized rats - Deepa S. Mandlik; Mitali P. Lavhale; Satish K. Mandlik (Inflammopharmacology, 2026)

Functional and Genomic Insights into Clostridium butyricum MCC0233: Probiotic Features and Safety Assessment - Vaidehi Pisu; Advika Dhanorkar; Deepa Shetty; Shilpa Wagh; Sumit Singh Dagar; Neelam Kapse; Prashant K. Dhakephalkar (Probiotics and Antimicrobial Proteins, 2026)

Emerging technologies in watermelon juice Processing: Innovations in preservation and quality enhancement - G. Jeevarathinam; Vismaya K. Sachithanandhan; J. Deepa; V. Arun Prasath; S. Ganga Kishore; Punit Singh; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Control, 2026)

Oral delivery of an ustekinumab biosimilar with bioavailability comparable to subcutaneous administration in healthy human participants - Joshua T. Myers; Alyson Yamaguchi; Kyle Horlen; Leonard C. Fung; April Toledo Vo; Deepa Mohan; Mary Hoopes; Mir Imran; Jacques Van Dam; Ofer M. Gonen; Mir A. Hashim; Arvinder K. Dhalla; et al. (European Journal of Clinical Pharmacology, 2026)

Fluoroquinolone Resistant Enterobacteriaceae Isolated from Bagmati River and its Tributaries in Kathmandu, Nepal - Santosh Khanal; Joshna Thapa; Deepa Neupane; Suman SK; Sudeep K C; Tista Prasai Joshi; Dev Raj Joshi (Water, Air, & Soil Pollution, 2026)

Cryopreservation of bael (Aegle marmelos L.Corr.) using encapsulated axillary buds - E. Deepa; Deepa S. Nair; Swapna Alex; K. B. Soni; M. M. Viji; B. Parvathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Nrf2 signaling in bone health: unlocking new avenues for osteoporosis management - Mitali P. Lavhale; Satish K. Mandlik; Vaibhav M. Shinde; Deepa S. Mandlik (Inflammopharmacology, 2025)

Probing the adhesion potential of Bifidobacterium animalis subsp. lactis MCM-B-2007 via in vitro and in silico analyses - Vaidehi Pisu; Neelam Kapse; Deepa Shetty; Shilpa Wagh; Sumit Singh Dagar; Prashant K. Dhakephalkar (Archives of Microbiology, 2025)

Spectroscopic Analysis of 4-MeO-TPA with Metal Oxide Nano-Assembly: Insights on Fluorescence Quenching and FRET - V. V. Koppal; R. Venkatesh; N. R. Banapurmath; Kalpana Sharma; Deepa H. K (Journal of Fluorescence, 2025)

The influence of climate modes on long-term sea level variability of the Indian ocean with special emphasis on the Southern Annular Mode: A study based on Indian ocean sea level reconstructions - J. S. Deepa; C. Gnanaseelan; K. V. Anusree (Theoretical and Applied Climatology, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Spectroscopic and Computational Analysis of 5PPD-CeO2: Insights from Fluorescence Quenching and FRET Studies - Kalpana Sharma; Varsha V. Koppal; Raviraj Kusanur; Deepa H. K (Journal of Fluorescence, 2025)

Genetic resources for enhancing drought tolerance from National Genebank collection of linseed (Linum usitatissimum L.) in India - Vikender Kaur; Devendra K. Payasi; Rakesh Choudhary; Vishnu Kumar; Shashank K. Yadav; Devender Singh; Vinay Kumar; Balram Jat; Deepa Garg; Vishal Kumar Gupta; Sudhir Kumar; Viswanathan Chinnusamy; et al. (Plant and Soil, 2025)

Exploring bioactive natural products for treating neurodegenerative diseases: a computational network medicine approach targeting the estrogen signaling pathway in amyotrophic lateral sclerosis and Parkinson’s disease - Mayank Roy Chowdhury; Ramireddy Venkata Sai Reddy; Navaneeth K. Nampoothiri; Rajeswara Reddy Erva; Sudarshana Deepa Vijaykumar (Metabolic Brain Disease, 2025)

Investigation of the Synergistic Antibacterial Properties of a Gel Formulated from Green-Synthesized Chitosan-Coated Copper Oxide Nanocomposite - Swapna Paul; M. K. Deepa (Journal of Pharmaceutical Innovation, 2025)

Molecular Detection of Benzimidazole Resistance Associated with the F200Y Polymorphism in the β-Tubulin Gene of Ancylostoma caninum: First Report from India - Deepa Soman; R. Radhika; Bindu Lakshmanan; Asha Rajagopal; M. N. Priya; K. Syamala; Arun George (Acta Parasitologica, 2025)

Photocatalytic advancements and applications of titanium dioxide (TiO₂): Progress in biomedical, environmental, and energy sustainability - Karuppiah Nagaraj; Suriyan Radha; Christy G Deepa; K. Raja; Vanitha Umapathy; Nilesh Prakash Badgujar; Nikhil M Parekh; Thangavel Manimegalai; Lakshmanan Archana Devi; Chandrabose Uthra (Next Research, 2025)

Enhanced production of phenylpropanoid glycosides from in vitro cultures of Artanema sesamoides Benth - Elizabeth Jose; Soni K. B.; Ancy Joseph; Swapna Alex; Deepa S. Nair (In Vitro Cellular & Developmental Biology - Plant, 2025)

Unique humoral immune response of pigs to repeated natural Japanese encephalitis virus infections: an amplifying host perspective - M. Dhanalakshmi; Himani Dhanze; Akash Mote; N. Narmatha; K. Sibi Thomas; R. Nithiaselvi; Deepa Mehta; M. Suman Kumar; K. N. Bhilegaonkar (Archives of Virology, 2025)

Genetic diversity and population structure analysis in tamarind (Tamarindus indica L.) using SCoT and SRAP markers - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; D. C. Lakshmana Reddy; K. Prakash (Genetic Resources and Crop Evolution, 2025)

Sero-epidemiology and risk factor investigation for exposure to Japanese encephalitis virus in swine populations reared in climatically diverse regions of India - Akash Balasaheb Mote; Balbir B. Singh; Deepa Mehta; Sagar M. Patel; M. Dhanalakshmi; M. Suman Kumar; K. N. Bhilegaonkar; Himani Dhanze (Tropical Animal Health and Production, 2024)

Integrated systems pharmacology, molecular docking, and MD simulations investigation elucidating the therapeutic mechanisms of BHD in Alzheimer’s disease treatment - Mayank Roy Chowdhury; Karamveer Karamveer; Basant K Tiwary; Navaneeth K Nampoothiri; Rajeswara Reddy Erva; Vijaykumar Sudarshana Deepa (Metabolic Brain Disease, 2024)

Controlled in vivo intrinsic detrimental effect of d-Limonene channelized by influential proximal interaction through apoptosis and steatosis in embryonic zebrafish (Danio rerio) - Anmol Choudhury; Sudakshya S. Lenka; Abha Gupta; Deepa Mandal; Adrija Sinha; Utsa Saha; Shaikh Sheeran Naser; Dibyangshee Singh; Faizan Zarreen Simnani; Aishee Ghosh; Shalini Kumari; Apoorv Kirti; et al. (Science of The Total Environment, 2024)

Development of dual stress-tolerant rice variety Jyothi with Saltol and Sub1 genes through marker-assisted backcross breeding - Deepa John; P. C. Rohini; K. S. Shylaraj (Cereal Research Communications, 2024)

Diagnostic efficacy of urinary neutrophil gelatinase-associated lipocalin and kidney injury molecule-1 for early detection of acute kidney injury in dogs with leptospirosis or babesiosis - M. Asma Idress; P. M. Deepa; R. L. Rathish; K. Vinodkumar; M. Pradeep (Veterinary Research Communications, 2024)

Extraction of Natural Pigment Curcumin from Curcuma Longa: Spectral, DFT, Third-order Nonlinear Optical and Optical Limiting Study - S. Deepa; S. Madhu; S. Devasenan; G. Murali; Pattath D. Pancharatna; M. Maaza; K. Kaviyarasu; S. Jeyaram (Journal of Fluorescence, 2024)

Innovative agricultural diagnosis: DQRR-AFH algorithm model for effective leaf disease prevention and monitoring - S. L. Bharathi; N. Deepa; J. Sathya Priya; K. Muthulakshmi (Earth Science Informatics, 2024)

Forced expression of microRNA-221-3p exerts protective effects against manganese-induced cytotoxicity in human lung epithelial cells - Deepa Gandhi; Sneha Bhandari; Sehal Mishra; Ashwinkumar P. Rudrashetti; Umashankar Vetrivel; Rajesh K. Thimmulappa; Subbiah Rajasekaran (Toxicology and Applied Pharmacology, 2024)

Recent progress and major gaps in the vaccine development for African swine fever - M. S Chandana; Sonu S. Nair; V. K. Chaturvedi; Abhishek; Santanu Pal; Manchikanthi Sri Sai Charan; Shilpa Balaji; Shubham Saini; Koppu Vasavi; Poloju Deepa (Brazilian Journal of Microbiology, 2024)

Phenotypic diversity in Tamarindus indica L. sourced from different provenances in India - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; K. Prakash (Agroforestry Systems, 2024)

Intracellular iron accumulation facilitates mycobacterial infection in old mouse macrophages - Stephen K. Kotey; Xuejuan Tan; Owen Fleming; Ramakrishnama Raju Kasiraju; Audrey L. Dagnell; Kyle N. Van Pelt; Janet Rogers; Steven D. Hartson; Nidheesh Thadathil; Ramasamy Selvarani; Rojina Ranjit; Sreemathi Logan; et al. (GeroScience, 2023)
Aging has a significant impact on the immune system, leading to a gradual decline in immune function and changes in the body’s ability to respond to bacterial infections. Non-tuberculous mycobacteria (NTM), also known as atypical mycobacteria or environmental mycobacteria, are commonly found in soil, water, and various environmental sources. While many NTM species are considered opportunistic pathogens, some can cause significant infections, particularly in individuals with compromised immune systems, such as older individuals. When mycobacteria enter the body, macrophages are among the first immune cells to encounter them and attempt to engulf mycobacteria through a process called phagocytosis. Some NTM species, including Mycobacterium avium ( M. avium ) can survive and replicate within macrophages. However, little is known about the interaction between NTM and macrophages in older individuals. In this study, we investigated the response of bone marrow–derived macrophage (BMMs) isolated from young (5 months) and old (25 months) mice to M. avium serotype 4, one of the main NTM species in patients with pulmonary NTM diseases. Our results demonstrated that BMMs from old mice have an increased level of intracellular iron and are more susceptible to M. avium serotype 4 infection compared to BMMs from young mice. The whole-cell proteomic analysis indicated a dysregulated expression of iron homeostasis–associated proteins in old BMMs regardless of mycobacterial infection. Deferoxamine, an iron chelator, significantly rescued mycobacterial killing and phagolysosome maturation in BMMs from old mice. Therefore, our data for the first time indicate that an intracellular iron accumulation improves NTM survival within macrophages from old mice and suggest a potential application of iron-chelating drugs as a host-directed therapy for pulmonary NTM infection in older individuals.

Cross-species transferability of IRAP retrotransposon markers and polymorphism in black pepper (Piper nigrum L.) - Manjushri Dinkar Dongare; Swapna Alex; K. B. Soni; K. P. Sindura; Deepa S. Nair; Roy Stephen; Elizabeth Jose (Genetic Resources and Crop Evolution, 2023)

Comparative analysis of VMT genes/proteins in selected plant species with emphasis on bread wheat (Triticum aestivum L.) - Hemant Sharma; Shayaba; Rahul Kumar; Jitendra Kumar; Deepa Bhadana; Ritu Batra; Rakhi Singh; Sachin Kumar; Joy K Roy; Harindra S. Balyan; Pushpendra K. Gupta (Genes & Genomics, 2023)

Effect of ZSB with Graded Levels of Zinc Fertilizer on Yield and Zinc Uptake Under Maize Cultivation - Deepa Verma; Ram Hari Meena; Aradhana Sukhwal; Gajanand Jat; Subhash Chandra Meena; Sudhir K. Upadhyay; Devendra Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Isolation and Chemical Structural Elucidation of Antibacterial Bioactive Compounds from Endophytic Fungal Strain Phoma sp. D1 - Suneel Kumar; Ravindra Prasad Aharwal; Deeksha Singh; Deepa Mishra; Ashish K. Sarangi; Ranjan K. Mohapatra; Ashwani Kumar Sharma; Sardul Singh Sandhu (Current Pharmacology Reports, 2023)

Galactosylgalactosylxylosylprotein 3-beta-glucuronosyltransferase—a potent biomarker for the diagnosis of tuberculosis in elephants - Ranjini Manuel; P. M. Deepa; R. U. Ashok; Rajeshkumar; K. Vijayakumar; K. Karthiayini; A. Janus (European Journal of Wildlife Research, 2022)

Sequential Profiling of Anti-SARS CoV-2 IgG Antibody in Post COVID-19 Patients - Ajaikumar Sukumaran; Rhema Elizabeth Thomas; R. Arun Krishnan; Thushara Thomas; Riji Thomas; Deepa K. Vijayan; Jofy. K. Paul; D. M. Vasudevan (Indian Journal of Clinical Biochemistry, 2022)

Assessment of Spatial and Temporal Changes in Water Quality of a Tropical River in Southern Western Ghats, Kerala, India, Using Physicochemical Quality Indices and Multivariate Analysis - Ajoy Saha; T. T. Paul; Deepa Sudheesan; Sravan Kumar Sharma; V. R. Suresh; B. K. Das; S. Manoharan; M. E. Vijaykumar; S. Samanta; Chayna Jana (Natural Resources Research, 2022)

Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features - K. V. Aneesh Kumar; M. P. Rajeeshkumar; M. Hashim; K. P. Deepa; J. L. Otero-Ferrer; N. Saravanane; Sujitha Thomas; K. K. Bineesh; V. M. Tuset (Marine Biology Research, 2022)

Investigation of Kinetic Drug Release Characteristics and In Vitro Evaluation of Sustained-Release Matrix Tablets of a Selective COX-2 Inhibitor for Rheumatic Diseases - M. Karthikeyan; M. K. Deepa; E. Bassim; C. S. Rahna; K. R. Sree Raj (Journal of Pharmaceutical Innovation, 2021)

Eco-friendly synthesis of phytochemical-capped iron oxide nanoparticles as nano-priming agent for boosting seed germination in rice (Oryza sativa L.) - Shadma Afzal; Deepa Sharma; Nand K. Singh (Environmental Science and Pollution Research, 2021)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Impact of climate on the evolution of vegetation in tectonically active Karewa basin, Kashmir Himalayas - Anjum Farooqui; Suresh K Pillai; Deepa Agnihotri; Salman Khan; Rajni Tewari; Sunil K Shukla; Sajid Ali; Anjali Trivedi; S K Pandita; Kamlesh Kumar; G D Bhat; Rajesh Agnihotri (Journal of Earth System Science, 2021)

Optimization and scale-up of laccase production by Bacillus sp. BAB-4151 isolated from the waste of the soap industry - T. Deepa; A. K. Gangwane; R. Z. Sayyed; H. P. Jadhav; Mehjabeen (Environmental Sustainability, 2020)

Fine mapping and gene cloning in the post-NGS era: advances and prospects - Deepa Jaganathan; Abhishek Bohra; Mahendar Thudi; Rajeev K. Varshney (Theoretical and Applied Genetics, 2020)
Improvement in traits of agronomic importance is the top breeding priority of crop improvement programs. Majority of these agronomic traits show complex quantitative inheritance. Identification of quantitative trait loci (QTLs) followed by fine mapping QTLs and cloning of candidate genes/QTLs is central to trait analysis. Advances in genomic technologies revolutionized our understanding of genetics of complex traits, and genomic regions associated with traits were employed in marker-assisted breeding or cloning of QTLs/genes. Next-generation sequencing (NGS) technologies have enabled genome-wide methodologies for the development of ultra-high-density genetic linkage maps in different crops, thus allowing placement of candidate loci within few kbs in genomes. In this review, we compare the marker systems used for fine mapping and QTL cloning in the pre- and post-NGS era. We then discuss how different NGS platforms in combination with advanced experimental designs have improved trait analysis and fine mapping. We opine that efficient genotyping/sequencing assays may circumvent the need for cumbersome procedures that were earlier used for fine mapping. A deeper understanding of the trait architectures of agricultural significance will be crucial to accelerate crop improvement.

Near reef abundance and on–offshore distribution of tuna larvae around Minicoy Island in Lakshadweep Sea, India - K. V. Aneesh Kumar; K. P. Deepa; M. M. Muhammed Rafeeq; G. Sree Renjima; Hashim Manjebrayakath; B. R. Smitha; N. Saravanane; M. P. Prabhakaran; V. N. Sanjeevan; M. Sudhakar (Marine Biology Research, 2020)

Genetic mapping of the European canker (Neonectria ditissima) resistance locus Rnd1 from Malus ‘Robusta 5’ - Vincent G. M. Bus; Reiny W. A. Scheper; Monika Walter; Rebecca E. Campbell; Biff Kitson; Lauren Turner; Brent M. Fisher; Sarah L. Johnston; Chen Wu; Cecilia H. Deng; Gagandeep Singla; Deepa Bowatte; et al. (Tree Genetics & Genomes, 2019)

Calcium alginate encapsulated synthetic seed production in Plumbago rosea L. for germplasm exchange and distribution - Anand Vishnu Prakash; Deepa S. Nair; Swapna Alex; K. B. Soni; M. M. Viji; B. R. Reghunath (Physiology and Molecular Biology of Plants, 2018)

Synthesis of magnetic carbon nanocomposites by hydrothermal carbonization and pyrolysis - M. T. H. Siddiqui; Sabzoi Nizamuddin; Humair Ahmed Baloch; N. M. Mubarak; Deepa K. Dumbre; Inamuddin; Abdullah M. Asiri; A. W. Bhutto; Madapusi Srinivasan; G. J. Griffin (Environmental Chemistry Letters, 2018)

Potential of native cold tolerant plant growth promoting bacilli to enhance nutrient use efficiency and yield of Amaranthus hypochondriacus - Chitra Pandey; Yogesh Kumar Negi; D. K. Maheshwari; Deepa Rawat; Deepti Prabha (Plant and Soil, 2018)

Isolation and Characterization of Fusarium verticillioides NKF1 for Unsaturated Fatty Acid Production - R. Manjoo; S. Deepa; Alok K. Yadav; Nand K. Singh (Current Microbiology, 2017)

Occurrence of a rare gigantic sized deep-sea cod Lepidion inosimae (Günther, 1887) in the Northwestern Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

Fluoride-Induced Oxidative and Inflammatory Stress in Osteosarcoma Cells: Does It Affect Bone Development Pathway? - Deepa Gandhi; Pravin K. Naoghare; Amit Bafana; Krishnamurthi Kannan; Saravanadevi Sivanesan (Biological Trace Element Research, 2017)

The influence of diesel—truck exhaust particles on the kinetics of the atmospheric oxidation of dissolved sulfur dioxide by oxygen - Vimlesh Kumar Meena; Yogpal Dhayal; Deepa Saxena; Ashu Rani; C. P. Singh Chandel; K. S. Gupta (Environmental Science and Pollution Research, 2016)

First record of deep-sea gigantic pycnogonid Colossendeis colossea Wilson, 1881 from the Western Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2016)

Comparative Transcriptome Analysis of Two Species of Curcuma Contrasting in a High-Value Compound Curcumin: Insights into Genetic Basis and Regulation of Biosynthesis - T. E. Sheeja; K. Deepa; R. Santhi; B. Sasikumar (Plant Molecular Biology Reporter, 2015)

Fructose induces mitochondrial dysfunction and triggers apoptosis in skeletal muscle cells by provoking oxidative stress - Natasha Jaiswal; Chandan K. Maurya; Deepti Arha; Deepa R. Avisetti; Ayyappan Prathapan; Palayyan S. Raj; Kozhiparambil G. Raghu; Shasi V. Kalivendi; Akhilesh Kumar Tamrakar (Apoptosis, 2015)

Genotyping-by-sequencing based intra-specific genetic map refines a ‘‘QTL-hotspot” region for drought tolerance in chickpea - Deepa Jaganathan; Mahendar Thudi; Sandip Kale; Sarwar Azam; Manish Roorkiwal; Pooran M. Gaur; P B Kavi Kishor; Henry Nguyen; Tim Sutton; Rajeev K. Varshney (Molecular Genetics and Genomics, 2015)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

A simple and efficient protocol for isolation of high quality functional RNA from different tissues of turmeric (Curcuma longa L.) - K. Deepa; T. E. Sheeja; R. Santhi; B. Sasikumar; Anu Cyriac; P. V. Deepesh; D. Prasath (Physiology and Molecular Biology of Plants, 2014)

Integrated physical, genetic and genome map of chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Reyazul Rouf Mir; Sabhyata Bhatia; Mahendar Thudi; Yuqin Hu; Sarwar Azam; Yong Zhang; Deepa Jaganathan; Frank M. You; Jinliang Gao; Oscar Riera-Lizarazu; Ming-Cheng Luo (Functional & Integrative Genomics, 2014)

Genetic dissection of drought tolerance in chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Mahendar Thudi; Spurthi N. Nayak; Pooran M. Gaur; Junichi Kashiwagi; Lakshmanan Krishnamurthy; Deepa Jaganathan; Jahnavi Koppolu; Abhishek Bohra; Shailesh Tripathi; Abhishek Rathore; Aravind K. Jukanti; et al. (Theoretical and Applied Genetics, 2014)

An Efficient Analytical Method for Analysis of Spirotetramat and its Metabolite Spirotetramat-Enol by HPLC - Soudamini Mohapatra; M. Deepa; G. K. Jagadish (Bulletin of Environmental Contamination and Toxicology, 2012)

Residue Dynamics of Tebuconazole and Quinalphos in Immature Onion Bulb with Leaves, Mature Onion Bulb and Soil - Soudamini Mohapatra; M. Deepa; G. K. Jagdish (Bulletin of Environmental Contamination and Toxicology, 2011)

Growth enhancement of black pepper (Piper nigrum) by a newly isolated Bacillus tequilensis NII-0943 - Syed G. Dastager; C. K. Deepa; Ashok Pandey (Biologia, 2011)

Behavior of Beta Cyfluthrin and Imidacloprid in/on Mango (Mangifera indica L.) - Soudamini Mohapatra; M. Deepa; G. K. Jagadish (Bulletin of Environmental Contamination and Toxicology, 2011)

Paracoccus niistensis sp. nov., isolated from forest soil, India - Syed G. Dastager; C. K. Deepa; Wen-Jun Li; Shu-Kun Tang; Ashok Pandey (Antonie van Leeuwenhoek, 2011)

Potential plant growth-promoting activity of Serratia nematodiphila NII-0928 on black pepper (Piper nigrum L.) - Syed G. Dastager; C. K. Deepa; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2011)

Persistence and Dissipation of Fluopicolide in/on Grape Berries and Soil Under Semi Arid Tropical Climatic Conditions of India - Soudamini Mohapatra; A. K. Ahuja; M. Deepa; G. K. Jagdish; N. Rashmi; Sampath Kumar; G. S. Prakash (Bulletin of Environmental Contamination and Toxicology, 2011)

Residues of Acephate and its Metabolite Methamidophos in/on Mango Fruit (Mangifera indica L.) - Soudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma (Bulletin of Environmental Contamination and Toxicology, 2011)

Plant growth-promoting activity in newly isolated Bacillus thioparus (NII-0902) from Western ghat forest, India - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

Persistence and Dissipation of Flubendiamide and Des-iodo Flubendiamide in Cabbage (Brassica oleracea Linne) and Soil - Soudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagadish; N. Rashmi (Bulletin of Environmental Contamination and Toxicology, 2010)

Isolation and characterization of plant growth promoting bacteria from non-rhizospheric soil and their effect on cowpea (Vigna unguiculata (L.) Walp.) seedling growth - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

Fate of Fipronil and its Metabolites in/on Grape Leaves, Berries and Soil Under Semi Arid Tropical Climatic Conditions - Soudamini Mohapatra; M. Deepa; G. K. Jagdish; N. Rashmi; Sampath Kumar; G. S. Prakash (Bulletin of Environmental Contamination and Toxicology, 2010)

Antifungal activity of Datura stramonium, Calotropis gigantea and Azadirachta indica against Fusarium mangiferae and floral malformation in mango - K. Usha; B. Singh; P. Praseetha; N. Deepa; D. K. Agarwal; R. Agarwal; A. Nagaraja (European Journal of Plant Pathology, 2009)

Human eosinophil-derived neurotoxin: involvement of a putative non-catalytic phosphate-binding subsite in its catalysis - Deepa Sikriwal; Divya Seth; Punyatirtha Dey; Janendra K. Batra (Molecular and Cellular Biochemistry, 2007)

Effectiveness of Treatment Technologies for Wastewater Pollution Generated by Indian Pulp Mills - Deepa K. Tiku; Anil Kumar; S. Sawhney; V. P. Singh; Rita Kumar (Environmental Monitoring and Assessment, 2007)

Structure of the extended diarrhea-inducing domain of rotavirus enterotoxigenic protein NSP4 - R. Deepa; C. Durga Rao; K. Suguna (Archives of Virology, 2007)

Phosphate starvation responses are mediated by sugar signaling in Arabidopsis - Athikkattuvalasu S. Karthikeyan; Deepa K. Varadarajan; Ajay Jain; Michael A. Held; Nicholas C. Carpita; Kashchandra G. Raghothama (Planta, 2007)

Pyruvate modulates antioxidant status of cultured human lens epithelial cells under hypergalactosemic conditions - Ipseeta Mohanty; Sujata Joshi; Deepa Trivedi; Sushma Srivastava; Radhika Tandon; Suresh K. Gupta (Molecular and Cellular Biochemistry, 2002)

Role of catalytic function in the antiplatelet activity of phospholipase A2 cobra (Naja naja naja) venom - L.M.S Rudrammaji; K. Deepa Machiah; T.P. Krishna Kantha; T. Veerabasappa Gowda (Molecular and Cellular Biochemistry, 2001)

Effect of methyl isocyanate (MIC) on rat erythrocytes - Deepa Agrawal; G. S. D. Gupta; J. S. Shukla; K. K. Dutta; P. K. Ray (Archives of Toxicology, 1990)